Unravelling the Power of Omics for the Infertile Aging Male - Bastos, Paulo; Freitas, Maria J.; Gomes, Andre; Vitorino, Rui; Fardilha, Margarida (Current Pharmaceutical Design, 2017)
The aging phenomenon is intrinsically responsible for diseases and lifestyle-associated conditions afflicting the aging male. In particular, male infertility seems to result from deleterious lifestyle choices. However, the aging effect at the individual gene/protein level is poorly discussed and valuable information is certainly missing. We have thus used an omics approach to identify differentially expressed proteins and genes from spermatozoa and seminal plasma samples across several conditions affecting adult male fertility. Our search resulted in 400 differentially expressed proteins in seminal plasma and 409 differentially expressed proteins in spermatozoa as well as, almost 6,000 differentially expressed spermatozoa mRNAs. We have functionally analyzed these proteins and genes to understand and discuss how biological processes and signaling pathways associated with aging might affect male fertility. Sperm and seminal fluid proteins from infertile males display significant alterations in i) processes previously implicated in the aging phenomena, such as mitochondrial dysfunction, DNA instability, oxidative stress, protein misfolding and intracellular mistrafficking, and ii) processes specifically involved in reproductive phenomena, such as sperm-egg recognition/acrosome reaction, embryo and morula development, blastocyst implantation and DNA methylation involved in embryo development. These proteins display a widespread distribution and seem to be significantly influenced by deleteriously lifestyle choices. Conventional assays to assess male fertility are inadequate to comprehensively reveal the broad-spectrum of alterations at the transcriptional and translational levels afflicting the infertile aging male. In turn, proteomics and transcriptomics are suitable options for addressing these key issues that may explain many poorly understood fertility-associated phenomena resulting from the aging process.
Keywords: Male infertility